(Flavour Fixation of Pepper - Endah Djubaedah; Tuti Puja Astuti (Warta Industri Hasil Pertanian, 1994)
The research was aimed at studying the quality changes of flavour fixatives of pepper (pipernigrum)during storage and its acceptance by costemers.Two fixation formulas were made i.e. (a)cellulose microcrystalline/sorbitol, and (b)cellulose microcrystalline/sucrose.shelf life of the fixative product were tested every 2 weeks for 6 weeks on their piperin content,microbes,aroma stability,and preference test on aroma and taste.The product of (b)was relatively better than those of (a) in iterms of its piperin content which was 0.70% and the reduction  of aroma was  o,80% after 6 weeks of storage,while the product of (a)had piperin content of 0,60% and the reduction of aroma was 4,8% after 6 weeks.Taste panel showed that the product using sorbitol was prefered to those of sucrase.The shelf did not changes after 6 weeks